Irrigação subsuperficial deficitária no cultivo de tomateiro em casa de vegetação - Mendonça, Thaís Grandizoli (2017)
The tomato is a demanding crop in regards to water and is among the most consumed vegetables in Brazil. The search for alternatives to improve tomato productivity, as well as reduce the water use in the crop cycle, is essential for agricultural production and environment. The objectives of this work were to evaluate the contribution of subsurface drip irrigation to yield and fruit quality of Grape tomatoes and to estimate the water use efficiency (EUA). The experiment was carried out in the CCA / UFSCar and consisted of three treatments with four randomized blocks. Irrigation management considered the storage soil water capacity (CAD), the soil moisture being high according to the water content reference of the treatment, 0.33 (T1), 0.29 (T2) and 0.25 m3 m-3 (T3), corresponding to 100 % replacement of CAD, and deficit irrigations of 75 and 50 % of CAD, respectively. Water content was monitored by TDR probes and the roots depth obtained through a root images scanner. The Grape tomatoes were transplanted under drip lines installed at 0.20 m depth. Quantitative and qualitative characteristics of the fruits were evaluated in relation to the proposed treatments, being: fruits number per plant, average fruit mass and productivity, quantitative characteristics and; Diameter, length, soluble solids, fruit pH and dry mass of leaves and stem, qualitative characteristics. The total water applied was 1297 mm in T1, 471 mm in T2 (36 % of water applied in T1) and 234 mm in T3 (18 % of T1). Among the characteristics evaluated, the T2 did not differ from the T1 treatment, except in the diameter and pH. The T3 treatment was equal to T1 only in the fruits number per plant. The average fruit mass was different among all treatments and there was no difference between soluble solids values. The T3 treatment obtained higher EUA, followed by T2 and T1, but did not have higher productivity nor better results in other evaluated attributes. Deficit subsurface irrigation of 75 % of CAD did not interfere in Grape tomato productivity and fruit quality, being the most recommended because of qualitative and quantitative attributes similar to full irrigation and to increase the EUA. It is concluded that deficit subsurface irrigation had productivity and fruit quality of Grape tomatoes like full irrigation when used 75 % of CAD, increased the water use efficiency and contributed with water use reduction in crop cycle.